On one of the syntactic peculiarities of the novel "Devil" by L. Tolstoy - HOVHANNESYAN, GAYANE (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper studies some syntactic features of the mentioned novel expressing the inner world of the main character. That is the reflection of contradiction so typical to Tolstoy's later period. According to the author's observations the main element of the novel is contradiction which is expressed with the help of adversative conjunctions.
Keywords: stylistic context, stylistic method, semantic-syntactic structure, contrastive comparison, adversative conjunctions